(untitled) - Frei, Frances X. (Boston, Massachusetts, 2012)
Most companies treat service as a low-priority business operation, keeping it out of the spotlight until a customer complains. Then service gets to make a brief appearance – for as long as it takes to calm the customer down and fix whatever foul-up jeopardized the relationship.
Keywords: Quan hệ khách hàng,Customer relations